2018
DOI: 10.1177/2045893218755987
|View full text |Cite
|
Sign up to set email alerts
|

Potential biomarkers and targets in reversibility of pulmonary arterial hypertension secondary to congenital heart disease: an explorative study

Abstract: Whether pulmonary arterial hypertension (PAH) is reversible in congenital heart disease (CHD) is important for the operability of CHD. However, little is known about that. Our research was aimed at exploring novel biomarkers and targets in the reversibility of CHD-PAH. CHD-PAH patients diagnosed with right heart catheterization (RHC) were enrolled (n = 14). Lung biopsy was performed during the repair surgery. After one year follow-up, mean pulmonary arterial pressures (mPAP) were evaluated by RHC to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 28 publications
5
24
0
1
Order By: Relevance
“…To explore the pathogenetic mechanism of irreversible CHD‐PAH, proteomics comparison of the lung tissues in both reversible and irreversible CHD‐PAH patients as well as in normal were performed. Proteomic analysis showed that transgelin was significantly up‐regulated (2.5‐fold) in irreversible CHD‐PAH group compared to the reversible and control group . Immunohistochemical staining and Western blot also confirmed the findings, and the expression of transgelin was significantly positively related with pathological grading of pulmonary arterioles.…”
Section: Introductionsupporting
confidence: 59%
“…To explore the pathogenetic mechanism of irreversible CHD‐PAH, proteomics comparison of the lung tissues in both reversible and irreversible CHD‐PAH patients as well as in normal were performed. Proteomic analysis showed that transgelin was significantly up‐regulated (2.5‐fold) in irreversible CHD‐PAH group compared to the reversible and control group . Immunohistochemical staining and Western blot also confirmed the findings, and the expression of transgelin was significantly positively related with pathological grading of pulmonary arterioles.…”
Section: Introductionsupporting
confidence: 59%
“…Seemingly contradictory, caveolin-1 is known to amplify beneficial BMPR2 signalling in ECs,42 and mutations or loss of caveolin-1 in ECs are generally associated with the development of PAH. However, caveolin-1 expression was indeed found to increase with disease progression in the media of remodelled arteries in end-stage IPAH and PAH-CHD 41. This temporal expression pattern makes caveolin-1 a potential marker to distinguish reversibility.…”
Section: Structural Functional and Molecular Assessment Of The Pulmomentioning
confidence: 94%
“…A recent study compared the metabolomics blood profiles of 10 early, reversible and four patients with advanced, irreversible PAH using mass spectrometry 41. In this small cohort, four candidate proteins were found with discriminative potential between groups: caveolin-1, filamin-1A, cathepsin-D (increased in irreversible PAH) and glutathione S-transferase mu1 (GSTM1; decreased in irreversible PAH).…”
Section: Structural Functional and Molecular Assessment Of The Pulmomentioning
confidence: 99%
See 1 more Smart Citation
“…14 Huang et al proposed some pathological biomarkers. 15 In irreversible PAH, they found increased expression of caveolin-1, filaminA, and cathepsin D and decreased glutathione S-transferase mu 1 (GSTM1) from a lung biopsy, which could be used as an expression profile to predict irreversible PAH caused by CHD. 15 Hopefully, new and improved methods to evaluate the histological findings, and the discovery of new biomarkers will lead to better understanding of the pathogenesis of PAH in patients with DS.…”
mentioning
confidence: 99%